Frontiers in applied environmental microbiology - Mukherji, K. G.; Pathak, N. C.; Cochin University of Science and Technology. School of Environmental Studies; National Symposium on "Frontiers in Applied Environmental Microbiology" (1995 : Cochin, India) (Lucknow : Print House, 1985)
Papers presented at the National Symposium on "Frontiers in Applied Environmental Microbiology" held in 1995 at Cochin, India
Includes index
Keywords: Microbial ecology -- Congresses; Sewage -- Microbiology -- Congresses; Soil pollution -- Congresses; Water -- Purification -- Congresses